Periodontal status and oral health knowledge among a selected population of Malaysian type 2 diabetics - Mastura M. Nordin; Syakirah A. Rahman; Renukanth P.C. Raman; Rathna D. Vaithilingam (Universiti Kebangsaan Malaysia, 2014)
Diabetes is an important risk factor in the pathogenesis of periodontal disease. Subjects with diabetes have a greater prevalence and severity of periodontal disease compared with subjects without diabetes. This study was carried out to assess periodontal status, treatment needs and oral health awareness among a selected population of Malaysian Type 2 diabetics. Ninety four Type 2 diabetes subjects were divided into those diagnosed with periodontal disease (PD+) (CPITN≥3) and healthy/gingivitis (PD-) (CPITN≤2) groups based on the Community Periodontal Index of Treatment Needs (CPITN). Subjects were interviewed regarding socio-demographic data and oral health awareness. Their medical information was obtained from the medical records. The results showed that 55.3% subjects had (PD+) as compared with 44.7% (PD-) subjects. 18.1% subjects required advanced periodontal treatment with specialist referrals. Male diabetic subjects were more likely to have advanced periodontal disease compared to female subjects (p<0.05). Subjects with advanced periodontal disease were more likely to be on combination of insulin and oral drugs (p<0.05). (PD+) diabetic subjects were aware that they had mobile teeth (p<0.001) and gum disease (p=0.004). In conclusion, male diabetics in Malaysia and subjects on combination of insulin and oral diabetic drugs are more likely to require advanced periodontal treatment.